Measurement and modeling of wireless body area network propagation characteristics of indoor environment at 10 GHz - Qin YANG; Lihua YANG; Lulu REN; Shanhu HUANG; Jiahuan LIU (物联网学报)
To explore the feasibility of high-frequency in indoor wireless body area network (WBAN) communication, the propagation characteristics of 10 GHz for WBAN in indoor scenario was given.Based on a large number of measurement data, the path loss, the shadow effect and the root-based delay spread of the 10 GHz were present, and a novel path loss model with the body angle was proposed, which utilizes the body angular factor to correct the path loss caused by the change of body angle.Meanwhile, the influence of receiving antenna at different heights of body on path loss was analyzed.Research results show that the path loss exponent has a quadratic function relationship with the body angle, the relationship between the path loss (PBA) caused by the body angle and the body angle can be expressed by a trigonometric function with a coefficient, which has a monotonously decreasing exponential function relationship with the distance between the receiving and sending ends.In addition, when the body is at different angles, the effect of the receiving ends in the human body on the path loss is smaller than when there is no body rotation angle.The above research results can provide the theoretical and practical basis for the use of 10 GHz indoor wireless body area network in the future.